Literatura para todos: análise das obras em função do público da EJA (Educação de Jovens e Adultos) - Chrisley Soares Felix (2009)
This research investigates the impact/benefits of the collection of books called Coleção Literatura para Todos in the Belo Horizonte schools. It will also be investigated the adequacy and ownership of this book collection for a target people: youth and adults who are newly literate or in the process of literacy. The main subject of this work was inspired on my own experience as a member of two groups named Proef I and GPELL. The knowledge of this existing book collection, my personal interest of using it with students and the needed to investigate the adequacy of this book collection in schools have built the perfect scenery to propose this research. So the important points discussed here were: the arrival of this book collection in Belo Horizonte schools and its adequacy for target people. The deal is to verify whether the public policy to encourage literacy can or can not contribute in the students formation as readers. Therefore an empirical research with a quality approach was carried out where literacy teachers, librarians and students were interviewed. The librarians were firstly questioned about the arrival of this book collection in the school and after about its using itself. The teachers were also questioned about the using and adequacy of this book collection to students. Finally the students who had been invited to read one of these books were accompanied in their experience to verify the adequacy of this book collection. Besides an interview it was also carried out a theoretical research which was based on discussions about reading itself, about the characteristics of the youth and adults in the process of literacy and finally a about the adequacy and ownership of this collection for the target people. So the results have shown two important points firstly: this book collection has not arrived in the schools as it should. Some teachers and librarians have not idea about this book collection. Second point shows that this book collection was inadequate for the target people. But for youth and adults who are newly literate and in a continuous process of learn this book collection can be adequate. Therefore the effort to develop a program with specific literary books which awaken the taste for literary reading has been inefficient for the target people